Coexistence of rod-like and lamellar eutectic growth patterns. (15th January 2022) - Bottin-Rousseau, Sabine; Witusiewicz, Victor T.; Hecht, Ulrike; Fernandez, Jose; Laveron-Simavilla, Ana; Akamatsu, Silvère
Abstract: We present the first observations of a large-scale coexistence between rod-like and lamellar eutectic growth patterns during directional solidification of a eutectic alloy. In situ experiments with real-time optical monitoring were carried out under microgravity onboard the International Space Station (ISS). We used the transparent succinonitrile-d, camphor eutectic alloy that ordinarily forms rod-like patterns. At low growth velocity, short lamellae stabilized at the contact line with a sample glass wall. In the presence of a controlled transverse temperature gradient, the coupled-growth pattern experienced a global drift along an inclined isotherm, and a stable lamellar domain spread over the solidification front. The propagative nature of the lamellar-to-rod transition was evidenced. The advance of the lamellar/rod domain boundary was determined by a slowly amplifying varicose instability of the lamellae. On a large scale, the domain boundary underwent a dynamic faceting. Graphical abstract: Image, graphical abstract